Community Empowerment Innovation Based on Local Wisdom in Environmental Management and the Green Economy in Ketegan Village, Taman District, Sidoarjo Regency - Rina Kharisma Wijayanti; Fedianty Augustinah; Eny Haryati (Educational Dynamics: International Journal of Education and Social Sciences, 2026)
This research examines the innovation of community empowerment rooted in local wisdom for environmental management and green economy advancement in Ketegan Village, Taman District, Sidoarjo Regency. The study stems from the increasing environmental issues resulting from urban development and the limited public understanding of sustainable economic measures. The research examines how local values—like cooperative efforts and social responsibility—can be incorporated into innovative, economically effective environmental management frameworks. Employing a qualitative descriptive method, data collection involved in-depth interviews, participatory observation, and the documentation of environmental policies and socio-economic information. The results indicate that residents of Ketegan have effectively created an empowerment model that integrates tradition and innovation via waste bank management, the use of organic waste for compost and biogas, and community-driven green economy projects engaging women and youth. Cooperation between the government, community, and universities has been essential in maintaining these initiatives. However, institutional capability, online marketing, and program viability continue to pose considerable obstacles. The research suggests enhancing community potential by providing training in green entrepreneurship, facilitating digital transformation, and incorporating local wisdom principles into sustainable development strategies. The results confirm that innovation rooted in local wisdom can effectively create resilient, competitive, and environmentally aware communities.